Maximum; Likelihood Estimation For The Non-Separable Spatial Unilateral Autoregressive Model. - Awang, Norhashidah; Shitan, Mahendran (2008)

(untitled)
Several classes of models have been proposed to describe the spatial processes. A special class of non-separable spatial unilateral model for modeling spatial data on two dimensional rectangular regular grid is the spatial autoregressive model, denoted by AR( PI ,1). In this paper, we establish a procedure to estimate the parameters of this model using the maximum likelihood method. We show that this procedure is practical and easy to be implemented We illustrate the procedure by fitting the AR(l, J) model to two set of data on the regular rectangular grid.